Penerapan Hygine dan Sanitasi Pada Departeman Food and Beverage Product di Restoran Papa's Limoncello Kuta Bali - Mertha, I Putu Adi; Putri Sri, Anak Agung; Sutaguna, I Nyoman Tri (Jurnal Kepariwisataan dan Hospitalitas, 2024)
Name : I Putu Adi Mertha Title : Application of Hygiene and Sanitation in Departemant Food and Beverage Product at Papa’s Limoncello Kuta Bali, Restaurant. Number of Pages : viii + 114 Pages Summary : In developing a restaurant, hygiene and sanitation aspects are important to note. Hygiene and sanitation will support the comfort, satisfaction and health of employees and consumers. This research was conducted at Papa’s Limoncello Restaurant located in Kuta, Bali. Papa’s Limoncello is a provider of food and beverage services with the concept of Italy menu specialties or authentic Italy cuisines. The variables in this study are the application of sanitation and hygiene which include Personal Hygiene, Hygiene and Sanitation of work environment, Hygiene and Sanitation of raw material selection. Data collection in this study was carried out by the method of observation, interviews,literature study and documentation. The informants in this study were Manager in Food and Beverage Product and then Supervisor in Food and Beverage Product at Papa’s Limoncello Restaurant. The data analysis technique used is descriptive qualitative. From the results of the study, obtained information related to the application of hygiene and sanitation in the Papa’s Limoncello Restaurant. In this research is described every aspect of Personal Hygiene, Hygiene and Sanitation of work environment, Hygiene and Sanitation of raw material selection that exist and not in the restaurant, along with documentation. E. Keywords: Application, Hygiene, Sanitation, Restaurant